Exploring Local Plant-Based Antimicrobials for Conservation of Art and Cultural Objects in Indonesia: A Review - Baroroh, Septiyana; Cahyandaru, Nahar (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Indonesia possesses a rich collection of art and cultural objects made from both organic and inorganic materials, which are highly susceptible to biodeterioration, particularly in the warm and humid tropical climate. Microorganisms are one of the primary causes of deterioration, leading to structural degradation, aesthetic changes, and the loss of historical and cultural value. Therefore, effective conservation strategies are needed to control the growth of microorganisms in conservation. This study examines various local plants used in traditional conservation in Indonesia, analyzing their bioactive compounds, effectiveness, and antimicrobial activity through a literature review. This study reviews various local plants used in traditional conservation in Indonesia by integrating ethnobotanical and microbiological conservation data from scientific literature. The analysis focuses on identifying bioactive compounds, reported antimicrobial activity, and their relevance to cultural material conservation. Findings indicate that Indonesian plants such as lemongrass, tobacco, clove, and nutmeg contain bioactive compounds with proven antimicrobial properties against microorganisms such as eugenol, alkaloids, citral, geraniol, monoterpenes and flavonoids. Although traditional conservation practices have been applied for a long time and have shown effectiveness, some of these practices lack scientific validation and require further research. Plant-based materials also generally have lower efficacy than synthetic chemicals, necessitating enhancement strategies such as nanoparticle technology. Further studies are essential to identify the mechanisms of active compounds in inhibiting microbial growth on cultural heritage objects, their long-term effectiveness, and their impact on various types of cultural materials. This study highlights the potential of local plants as antimicrobial agents in conservation of art and cultural objects. Further research is needed to optimize their application in modern conservation practices.